2005
DOI: 10.1007/s00381-005-0002-6
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous spinal epidural hematoma in a toddler—a case report

Abstract: Although rare SSEDH requires immediate surgical decompression to avoid any permanent neurological deficit. Reconstructive surgical procedures like laminotomy are preferred in children where the incidence of spinal deformity is high following laminectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 5 publications
0
21
0
Order By: Relevance
“…In our review of English literature, only eight cases below the age of 2 years had been reported with no age below the first year of life (Table 1). [4][5][6][7][8][9] The term 'crib death' has been used to describe sudden unexplained death of neonates. 10 In postmortem examination of infants with 'crib death', spinal epidural hematomas were the causal factor in 10% of cases.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In our review of English literature, only eight cases below the age of 2 years had been reported with no age below the first year of life (Table 1). [4][5][6][7][8][9] The term 'crib death' has been used to describe sudden unexplained death of neonates. 10 In postmortem examination of infants with 'crib death', spinal epidural hematomas were the causal factor in 10% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8][9] This region is more commonly affected as a result of significant disproportion of the weight ratio of the head to the body in pediatric population, in which the head proportion is larger and heavier than in adults. In addition, gaining the head control is an important neuromuscular development milestone during the first 4-6 months of life.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations